The role of left atrio-ventricular coupling index and left atrial ejection fraction in predicting onset of atrial fibrillation and adverse cardiac events in hypertrophic cardiomyopathy - Francesca, Parisi; Eluisa, La Franca; Lorenzo, Pistelli; Giovanni, Gentile; Diego, Bellavia; Vincenzo, Nuzzi; Paolo, Manca; Mulè, Massimiliano; Concetta, Zito; Gianluca, Di Bella; Carerj, Scipione; Manlio, Cipriani; et al. (Cardiovascular ultrasound, 2025)
Several predictors of atrial fibrillation (AF) onset in patients with hypertrophic cardiomyopathy (HCM) have been proposed, however, all of them showed limited accuracy. This study aims to assess the role of new echographic parameters in predicting AF onset and major adverse cardiovascular outcomes (cardiovascular death or heart transplantation). Clinical and imaging data from 141 patients with HCM and without a history of AF were retrospectively analyzed over a 5-year period. Patients who developed AF during the study were compared to those who did not. The analysis focused on key atrial parameters, including the Left Atrial Contraction Index (LACI) and Left Atrial Ejection Fraction (LAEF). LACI was defined as the ratio of left atrial end-diastolic volume to left ventricular end-diastolic volume. Echocardiographic measurements were standardized using cardiac magnetic resonance (CMR) as the reference. Regarding statistical analysis, each significant continuous variable was categorized by identifying a cut-off value using the Youden index. Independent associations with outcomes and cumulative survival were assessed using Cox regression analysis. Thirty-five patients developed AF, at a mean time of 4 years. The HCM-AF group had significantly higher values of LACI, left atrial diameter (LAD), and left atrial minimum volume (LAVmin). A LACI > 43% on echocardiography and LACI > 44% on CMR showed the best performance in identifying patients at risk for AF. In multivariate analysis, an echocardiographic LAEF < 43% was independently associated with the occurrence of AF (HR 2.9, 95% CI: 1.2-6.9). Additionally, a LAD > 40.5 mm was independently associated with AF onset, with a hazard ratio of 2.5 (95% CI 1.1-5.5). Eleven patients experienced the composite outcome of cardiovascular death or heart transplant, and a LACI > 60% was associated with this outcome. In patients with HCM, both LACI and LAEF were significantly associated with the occurrence of AF over a 4-year period, demonstrating higher sensitivity and specificity compared to other parameters. A LACI > 60% was also found to be associated with cardiovascular death or heart transplant in this population.